Assessment of antioxidant capacity, anti-collagenase and anti-elastase assays of Malaysian unfermented cocoa bean for cosmetic application - Abdul Wahab, Norliza; Abdul Rahman, Russly; Ismail, Amin; Mustafa, Shuhaimi; Hashim, Puziah (Omics Publishing Group, 2014)
Recent trends in anti-aging research projected the use of antioxidant compound derived from botanical products. Phenolic acids, flavonoids and high molecular weight polyphenols are some of antioxidants which are able to protect human skin against the harmful effects of ultraviolet irradiation, i.e. photoaging and skin cancer development. Various studies have demonstrated cocoa beans to contain polyphenols and possess health promoting effects mainly on antiradical property. In this study, the HPLC/DAD quantification of (–)-epicatechin from PBC123 and PBC140 Malaysian unfermented cocoa bean extracts (CBEs) were 121.01 and 118.09 mg/g DW, whereas concentration of (+)-catechin were 6.65 and 6.53 mg/g DW, respectively with no significant differences (p>0.05). In term of antioxidant capacity, Ferric reducing/antioxidant power of the respective clones were assayed at 822.10 and 795.99 mM FeSO4/g DW. Inhibition of proteinases expression induces by reactive oxygen species were exhibited in the anti-collagenase and anti-elastase assays. The anti-collagenase activity of PBC123 and PBC140 were 62.99% and 59.96% whereas anti-elastase has been measured at 36.60% and 15.75%, respectively. Positive and high correlation were observed within epicatechin content (1), FRAP (2) and anti-collagenase (3) with significant relationships for both PBC123 and PBC140 (r12=0.901, r13=0.768 and r23=0.908). A statistical One-Way ANOVA showed that there was no significant difference obtained between PBC123 and PBC140 in terms of epicatechin, FRAP and anti-collagenase assays, however, significant difference was observed from anti-elastase assessment (p<0.05).These results indicate unfermented PBC123 clone as a potential source of natural ingredient in a cosmetic industry.